Strategi Permainan Bisik Berantai untuk Meningkatkan Kemampuan Berbahasa Siswa Kelas I SD Negeri 1501 Hurung Jilok - Harahap, Rani Astria Silvera; Imelda Hasanah Dalimunte; Harahap, Nurhalimah (Yayasan Perguruan Kampus, 2025)
Based on this research it can be concluded that: (1) The language skills of students in grade I of SD Negeri 1501 Hurung Jilok in the pre-cycle obtained a total score of 1750, with an average of 62.50, the highest score was 80 and the lowest score was 40. The results of the pre-cycle student language skills test category “A” 7 students or 25.00%, the language skills of category “B” 7 students or 10.71%, the language skills of category “C” 7 students or 25.00%, the language skills of category “D” 4 students or 14.29% and the language skills of category “E” 7 students or 25.00%. (2) The application of the whispering game strategy to improve the language knowledge of first grade students of SD Negeri 1501 Hurung Jilok, namely in the language ability of students in cycle I obtained a total score of 2180, an average of 77.86, the highest score was 90 and the lowest score was 60. The results of the language ability test of students in cycle I category “A” or 10 students or 35.71%, the language ability of students in category “B” 7 students or 25.00%, the language ability of students in category “C” 6 students or 21.43%, the language ability of students in category “D” 5 students or 17.86% and there was no language ability of students in category “E”. The language ability of students in cycle II obtained a total score of 2370, with an average of 84.64, the highest score was 90 and the lowest score was 70. The results of the language ability test of students in cycle II in category “A” 15 students or 53.57%, the language ability of students in category “B” 11 students or 39.29%, the language ability of students in category “C” 2 students or 7.14%, no language ability of students in category “D” and no language ability of students in category “E”.